EFFICIENCY OF SHALLOT MARKETING IN WANASARI DISTRICT OF BREBES - Astrilia Devita Permataputri; Agus Setiadi; Kustopo Budiraharjo (Tadulako University, 2019)
This study aims to analyze the shallot marketing channels, analyze the efficiency of shallot marketing, and the factors affect the efficiency of shallot marketing in Wanasari, Brebes Regency. The study was conducted in December 2018 - January 2019 in Wanasari District, Brebes Regency. The sampling of farmers respondents was carried out by the proportionate stratified random sampling method involved 100 farmers. A snowball sampling technique with 22 traders was done for marketing agency respondents. The data collected, subsequently analyzed descriptively with marketing channel patterns. The marketing efficiency, farmer's share and RPM, and factors affecting marketing efficiency were also examined. This study indicates two marketing pattern channels for shallot seedlings and three patterns for consumption. Efficient marketing channels was only in pattern I. Besides, pattern II, III, and IV were found in less efficient marketing. In contrast, pattern III was an inefficient marketing channel. The multiple linear regression test showed that the coefficient of variable selling price of farmers was negative and had a significant effect on marketing efficiency. Coefficient of the variable consumer purchase price was positive and had a significant effect on marketing efficiency. Also, coefficient of the variable number of institutions involved was negative and had a significant effect on marketing efficiency.